علاقة الأبعاد الخمسة لمنظور الزمن وفق نظرية زمباردو بمستوى الطموح الأكاديمي لدى المراهق المتمدرس: دراسة على عينة من تلاميذ مرحلة التعليم الثانوي ببلدية الوادي - الأرقط عائشة (University Eloued جامعة الوادي, 2024)
تهدف الدراسة الحالية إلى التعرف على طبيعة العلاقة بين الأبعاد الخمسة لمنظور الزمن وفق نظرية زمباردو (Zimbardo, 1999) والطموح الأكاديمي لدى المراهق المتمدرس بالمرحلة الثانوية، كما تهدف إلى الكشف عن الاختلاف بين الأبعاد الخمسة لمنظور الزمن ومستوى الطموح الأكاديمي لدى المراهقين المتمدرسين. ولتحقيق أهداف هذه الدراسة اعتمدنا المنهج الوصفي، واستخدام المقياسين: مقياس منظور الزمن لزمباردو ترجمة وتقنين جارالله وشرفي (2012)، ومقياس الطموح الأكاديمي للرفاعي (2017) وتطبيقهما على عينة قوامها (450) من المراهقين المتمدرسين بالمرحلة الثانوية ببلدية الوادي، تم اختيارهم بطريقة عشوائية، وبعد المعالجة الإحصائية للبيانات باستخدام الحزمة الإحصائية للعلوم الاجتماعية (SPSS)، خلصت الدراسة إلى النتائج التالية: - يوجد اختلاف دال احصائيا بين الأبعاد الخمسة لمنظور الزمن وفق نظرية زمباردو (Zimbardo, 1999) لدى المراهقين المتمدرسين بالمرحلة الثانوية. - يتميز أغلبية المراهقين المتمدرسين بالمرحلة الثانوية بمستوى طموح أكاديمي منخفض. - يوجد اقتران دال احصائيا بين أبعاد منظور الزمن ومستويات الطموح الأكاديمي لدى المراهقين المتمدرسين. - لا يوجد اختلاف دال احصائيا بين الذكور والاناث من المراهقين المتمدرسين على مقياس الأبعاد الخمسة لمنظور الزمن. - لا يوجد اختلاف دال احصائيا بين المراهقين المتمدرسين على مقياس الأبعاد الخمسة لمنظور الزمن تبعا للمستوى الاقتصادي للأسرة. - توجد فروق دالة احصائيا بين الذكور والاناث من المراهقين المتمدرسين على مقياس الطموح الأكاديمي. وذلك لصالح الاناث. - توجد فروق دالة احصائيا بين المراهقين المتمدرسين على مقياس الطموح الأكاديمي تبعا للشعبة الدراسية(علمي/أدبي). وذلك لصالح الشعب العلمية. - توجد فروق دالة احصائيا بين المراهقين المتمدرسين المعيدين وغير المعيدين على مقياس الطموح الأكاديمي. وذلك لصالح المراهقين المتمدرسين غير المعيدين. - لا توجد فروق دالة احصائيا بين المراهقين المتمدرسين على مقياس الطموح الأكاديمي تعزى للمستويات الدراسية. - لا توجد فروق دالة احصائيا بين المراهقين المتمدرسين على مقياس الطموح الأكاديمي تعزى للمستويات الاقتصادية للأسر. وتم تفسير نتائج الدراسة ومناقشتها بالرجوع إلى الإرث النظري والدراسات السابقة والخروج ببعض المقترحات. Abstract The main objective of this study is to identify the nature of the relationship between the five dimensions of time perspective according to Zimbardo’s theory (1999) and the academic ambition of secondary school adolescents. It also aims to reveal the difference between the five dimensions of time perspective and the level of academic ambition among these adolescents. To achieve the objectives of this study, we adopted the descriptive approach and used two scales: the Time Perspective Scale by Zimbardo, translated and codified by Jarallah and Sharfi (2012), and the Academic Ambition Scale by Al-Rifai (2017), and applied them to a sample of (450) secondary school adolescents from EL Oued. They were chosen randomly. After statistical processing of the data using the Statistical Package for the Social Sciences (SPSS), the study concluded the following results: - There is a statistically significant difference between the five dimensions of time perspective according to Zimbardo’s theory (Zimbardo, 1999) among secondary school adolescents. The majority of teenagers attending secondary school are characterized by a low level of academic ambition. - There is a statistically significant correlation between the dimensions of time perspective and the levels of academic ambition among school adolescents. - There is no statistically significant difference between male and female school adolescents on the scale of the five dimensions of time perspective. - There is no statistically significant difference between schooled adolescents on the scale of the five dimensions of time perspective depending on the economic level of the family. - There are statistically significant differences between male and female school adolescents on the academic ambition scale. This is in favor of females. - There are statistically significant differences between school adolescents on the academic ambition scale according to the academic division (scientific/literary streams). This is in favor of scientific streams. - There are statistically significant differences between adolescent repeat students and non-repeated students on the academic ambition scale in favour of teenagers who are not repeat students. - There are no statistically significant differences between schooled adolescents on the academic ambition scale due to academic levels. - There are no statistically significant differences between schooled adolescents on the academic ambition scale due to the economic levels of families. The results of the study were interpreted and discussed by referring to the theoretical heritage and previous studies, and some proposals were made.
أطروحة دكتوراه تخصص علم النفس المدرسي كلية العلوم الاجتماعية والانسانية جامعة الوادي
Keywords: منظور الزمن; نظرية زمباردو; الطموح الأكاديمي; المراهق المتمدرس; Time perspective; Zimbardo theory; academic ambition; schooled adolescent